2015
DOI: 10.5713/ajas.15.0505
|View full text |Cite
|
Sign up to set email alerts
|

Production of Transgenic Pigs with an Introduced Missense Mutation of the Bone Morphogenetic Protein Receptor Type IB Gene Related to Prolificacy

Abstract: In the last few decades, transgenic animal technology has witnessed an increasingly wide application in animal breeding. Reproductive traits are economically important to the pig industry. It has been shown that the bone morphogenetic protein receptor type IB (BMPR1B) A746G polymorphism is responsible for the fertility in sheep. However, this causal mutation exits exclusively in sheep and goat. In this study, we attempted to create transgenic pigs by introducing this mutation with the aim to improve reproducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…A large number of studies have shown that the BMPR1B gene plays an active role in mammalian embryo development and follicular development (Tang et al, 2019;Yao et al, 2019; Abdurah- Note that different lowercase letters in the same column represent a significant difference (P < 0.05). man et al, 2019;Zhao et al, 2016). However, further studies are required to deeply investigate the relationship between BMPR1B and mammalian reproduction.…”
Section: Effect Of Bmpr1b Gene Expression On Mammalian Reproductionmentioning
confidence: 99%
“…A large number of studies have shown that the BMPR1B gene plays an active role in mammalian embryo development and follicular development (Tang et al, 2019;Yao et al, 2019; Abdurah- Note that different lowercase letters in the same column represent a significant difference (P < 0.05). man et al, 2019;Zhao et al, 2016). However, further studies are required to deeply investigate the relationship between BMPR1B and mammalian reproduction.…”
Section: Effect Of Bmpr1b Gene Expression On Mammalian Reproductionmentioning
confidence: 99%
“…1 A,B). The founder animal is known to have two insertion sites of the exogenous gene ( BMPR-1B ): one at the NAGLU locus on SSC12 and the other at the CMTM8 locus (within the first intron of the CMTM8 gene) on SSC13 ( Zhao et al, 2016 ). Primers F2/R2 and F3/R3 spanning the vector and host genome ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA was extracted from ear samples using phenol/chloroform method. Primers F1/R1 ( ) were implemented to identify transgenic and non-transgenic (WT) pigs as previously reported ( Zhao et al, 2016 ). Primers F2/R2 and F3/R3 ( ) were used to classify the transgenic individuals with one or two insertion sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucopolysaccharidosis IIIB (also known as Sanfilippo syndrome B) is caused by variants in the alpha-N-acetylglucosaminidase (NAGLU) gene and has been previously characterized at the clinical and molecular level in humans, emus 11 , cattle 12 , knockout mice 13 , and transgenic swine 14,15 . Furthermore, MPS IIIB has been clinicopathologically reported in Schipperke dogs (OMIA 001342-9615) 10 .…”
mentioning
confidence: 99%